2021
DOI: 10.1055/s-0041-1726028
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Topically Administered Heparin on Peripheral Microcirculation of the Skin: A Double-Blind, Randomized, Controlled Preliminary Study on 50 Healthy Subjects

Abstract: Background Venous thrombosis is the most common cause of flap failure in the first days after surgery. Although heparin is one of the most important antithrombotic substances and is implemented in the therapy of various diseases, there are only a few studies addressing its topical administration in the field of flap surgery. Especially, very little is known about the effects of topical heparin and its impact on microcirculation. In this study we evaluated to what extent topically administered heparin influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…The present results are in line with previous reports showing that, even if it was demonstrated that topical heparin is not able to modify coagulation parameters [9,10], yet topical heparin demonstrated positive local microcirculation changes as increased capillary venous oxygen saturation, increased blood filing of microvessels, increased blood flow and velocity [11,12] and enhanced fibrinolytic effect [13]. The reported effects were more prominent when topical heparin was aided by dexpanthenol as penetration enhancer [12,14]. However, the overall results from the present study confirm also the enhanced efficacy of topical heparin combined with an anti-inflammatory agent for the treatment of local trauma injuries versus topical heparin alone, as it was already signalled.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The present results are in line with previous reports showing that, even if it was demonstrated that topical heparin is not able to modify coagulation parameters [9,10], yet topical heparin demonstrated positive local microcirculation changes as increased capillary venous oxygen saturation, increased blood filing of microvessels, increased blood flow and velocity [11,12] and enhanced fibrinolytic effect [13]. The reported effects were more prominent when topical heparin was aided by dexpanthenol as penetration enhancer [12,14]. However, the overall results from the present study confirm also the enhanced efficacy of topical heparin combined with an anti-inflammatory agent for the treatment of local trauma injuries versus topical heparin alone, as it was already signalled.…”
Section: Resultssupporting
confidence: 93%
“…This different evolution can be explained by the depth and the magnitude of the injuries in Orthopedic and Traumatology clinic and by the fact that topical heparin induces mostly local superficial effects because topical heparin cannot follow diclofenac in systemic flow in clinically significant concentrations in order to induce intense and profound anti-inflammatory effect [4]. The present results are in line with previous reports showing that, even if it was demonstrated that topical heparin is not able to modify coagulation parameters [9,10], yet topical heparin demonstrated positive local microcirculation changes as increased capillary venous oxygen saturation, increased blood filing of microvessels, increased blood flow and velocity [11,12] and enhanced fibrinolytic effect [13]. The reported effects were more prominent when topical heparin was aided by dexpanthenol as penetration enhancer [12,14].…”
Section: Resultssupporting
confidence: 89%
“…In individuals with sensitive skin, exposure to rapid changes in physical and chemical conditions or variations in environmental temperature can lead to the rapid expansion of skin microvessels and increased blood fow, resulting in fushing of the skin [17]. In addition, the accelerated blood fow enhances the absorption of external irritants, increasing the likelihood of uncomfortable sensations such as itching, burning, or tingling [18].…”
Section: Discussionmentioning
confidence: 99%
“…Topical sodium heparin's main effect on uncomplicated superficial thrombophlebitis or superficial vein thrombosis is antiinflammatory. Venous disease, including varicose veins and chronic venous insufficiency, is one of the most frequently reported chronic conditions and a substantial source of morbidity [1][2][3]. Estimates of the incidence of venous disease vary widely by anatomic region and classification of pathology [4].…”
Section: Introductionmentioning
confidence: 99%